Molecular cytogenetic characterisation of a mosaic add(12)(p13.3) with an inv dup(3)(q26.31 --> qter) detected in an autistic boy - Carreira, IM (2012)
BACKGROUND: Inverted duplications (inv dup) of a terminal chromosome region are a particular subset of rearrangements that often results in partial tetrasomy or partial trisomy when accompanied by a deleted chromosome. Associated mosaicism could be the consequence of a post-zygotic event or could result from the correction of a trisomic conception. Tetrasomies of distal segments of the chromosome 3q are rare genetic events and their phenotypic manifestations are diverse. To our knowledge, there are only 12 cases reported with partial 3q tetrasomy. Generally, individuals with this genomic imbalance present mild to severe developmental delay, facial dysmorphisms and skin pigmentary disorders. RESULTS: We present the results of the molecular cytogenetic characterization of an unbalanced mosaic karyotype consisting of mos 46,XY,add(12)(p13.3) [56]/46,XY [44] in a previously described 11 years old autistic boy, re-evaluated at adult age. The employment of fluorescence in situ hybridization (FISH) and multicolor banding (MCB) techniques identified the extra material on 12p to be derived from chromosome 3, defining the additional material on 12p as an inv dup(3)(qter --> q26.3::q26.3 --> qter). Subsequently, array-based comparative genomic hybridization (aCGH) confirmed the breakpoint at 3q26.31, defining the extra material with a length of 24.92 Mb to be between 174.37 and 199.29 Mb. CONCLUSION: This is the thirteenth reported case of inversion-duplication 3q, being the first one described as an inv dup translocated onto a non-homologous chromosome. The mosaic terminal inv dup(3q) observed could be the result of two proposed alternative mechanisms. The most striking feature of this case is the autistic behavior of the proband, a characteristic not shared by any other patient with tetrasomy for 3q26.31 --> 3qter. The present work further illustrates the advantages of the use of an integrative cytogenetic strategy, composed both by conventional and molecular techniques, on providing powerful information for an accurate diagnosis. This report also highlights a chromosome region potentially involved in autistic disorders.